The social-cognitive play of selected Filipino children - Yuson, Cristina Lim (Maria Cristina Aldaba Lim) 1946-
The purposes of the study are to investigate the forms of cognitive play children engage in during social play and to determine whether significant differences exist between the free play behaviors of the lower and upper income groups and children attending pre-school and those who have never attended pre-school. Findings of the study seem to contradict the deficit theory of the low income group because the low income group and the high income group have no or very little significant differences in their play. Likewise, the study shows that schooling is the variable that manifests the significant differences in play.